Ten years of limnological monitoring of a modified natural lake in the tropics: Cote Lake, Costa Rica - Umaña, Gerardo (2014)
Lake Cote is the largest natural lake in Costa Rica. It is located 650m above sea level along the boundary between the North Caribbean and Pacific slopes, near the Southern end of the volcanic Guanacaste mountain range. In the early 1980s the lake’s main outlet was dammed and the outflow was diverted into Arenal Reservoir. Lake Cote was first studied in 1990-1991, and later in 2001, before it was again modified by raising its dam by one meter to use its outflow for hydroelectricity. From 2002 to 2010 it has been monitored twice a year for changes in its limnology. Here I present a summary of its basic characteristics and an analysis of their changes through time. The lake is discontinuous polymictic, and sometimes develops a thermocline at 6m depth that may last for several days as evidenced by the occasional development of an anoxic layer close to the bottom. Since its modification for hydropower production, the surface water temperature has attained higher values than before. Oxygen levels in the lake show periods of hypoxia to anoxia in the hypolimnion, that have become more frequent since modification. Despite its turbid water, the lake has low levels of nutrient concentrations and of chlorophyll a. The trend in these parameters in recent times is a reduction in chlorophyll a and an increase in water transparency, implying a reduction in primary productivity. These changes are discussed in relationship with anthropogenic factors such as the modification of the lake and its management, changes in landscape around the lake and global climate change.